A Biomechanical Comparison of 2 Hip Capsular Reconstruction Techniques: Iliotibial Band Autograft Versus Achilles Tendon Allograft. Issue 13 (November 2020) - Pasic, Nicholas; Burkhart, Timothy A.; Baha, Pardis; Ayeni, Olufemi R.; Getgood, Alan; Degen, Ryan M.
Background: Several techniques for hip capsular reconstruction have been described to address gross instability or microinstability due to capsular deficiency. However, objective biomechanical data to support their use are lacking. Purpose: To compare the kinematic effect of 2 capsular reconstruction techniques (iliotibial band [ITB] graft and Achilles tendon graft). Kinematic effect encompassed rotational range of motion (ROM) as well as joint translation in the coronal, sagittal, and axial planes. Study Design: Controlled laboratory study. Methods: 8 paired, fresh-frozen hemi-pelvises (16 hips) were tested on a custom-designed joint motion simulator in the intact state and after capsulectomy. Pairs were randomly allocated to either ITB or Achilles reconstruction and retested. Testing was performed at 0°, 45°, and 90° of flexion. Internal-external rotation (IR-ER) torques and abduction-adduction torques of 3 N·m were applied to the femur via a load cell at each position, and rotational ROM and joint translation in the coronal, sagittal, and axial planes were recorded. Results: At 45° and 90°, there was a significant effect of the condition of the hip on the total IR-ER ( P = .004, effect size [ES] = 0.305; and P < .001, ES = 0.497; respectively). At 45°, mean ± SD total rotation was significantly greater for the capsulectomy (59.7°± 15.9°) state compared with intact (53.3°± 13.2°; P = .007). At 90°, reconstruction significantly decreased total rotation to 49.0°± 18.9° compared with a mean total rotation of 52.8°± 18.7° after capsulectomy ( P = .02). No difference was seen in the total abduction-adduction of the hip between conditions. Comparisons of the 2 different reconstruction techniques showed no significant differences in total IR-ER or abduction-adduction ROM or joint translation in the coronal, sagittal, or axial planes. For translation, at both 0° and 45° there was a statistically significant effect of the condition on the medial-lateral translation ( P = .033; ES = 0.204). Reconstruction, independent of technique, was successful in significantly decreasing ( P = .030; P = .014) the mean medial-lateral translation at 0° and 45° of hip flexion from 5.2 ± 3.8 mm and 5.6 ± 4.0 mm to 2.8 ± 1.9 mm and 3.9 ± 3.2 mm, respectively. Conclusion: The integrity of the native hip capsule played a significant role in rotational stability, where capsulectomy significantly increased rotational ROM. Both ITB and Achilles reconstruction techniques restored normal rotational ROM of the hip at 90° of flexion as well as coronal plane stability at 0° and 45° of hip flexion. No differences were seen between ITB and Achilles reconstruction techniques. Clinical Relevance: Both capsular reconstruction techniques provide comparable joint kinematics, restoring rotation and translation to normal values with the exception of rotational ROM at 45°, which remained significantly greater than the intact state. The most significant results were the rotational stability at 90° of hip flexion and coronal plane stability at 0° and 45° of hip flexion, which were significantly improved compared with the capsulectomy state.